Pengaruh Motivasi dan Disiplin terhadap Kinerja Karyawan pada CV Dua Putra Mandiri Medan - Sandhi Fialy Harahap; Syati Manaharawan Siregar; Robby T anizar Abdillah Reza (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
Based on the results of initial research conducted on performance, it was found that there were problems in accordance with performance indicators, including: the quality of employees is still considered very low, the quantity of employees is still considered lacking in completing the work within the allotted time and also there is still a lack of commitment to work. This greatly hampers the performance of employees at CV Dua Putra Mandiri. The purpose of this study was to determine the effect of motivation and discipline on employee performance at CV Dua Putra Mandiri. This research uses associative method with quantitative descriptive approach. The types of data used in this study are primary and secondary data. Primary data is obtained from the results of direct processing of the object. While secondary data is data that researchers get from books and other data sources related to the discussion of this research. The research was conducted to determine the partial and simultaneous effect of the independent variable (X) on the dependent variable (Y). The results of this study indicate that partially it can be concluded that motivation (X1) and discipline (X2) have a positive and significant influence on performance (Y). From the results of this study, it can be concluded that simultaneously motivation and discipline have a significant effect on performance.